2017
DOI: 10.1097/rli.0000000000000394
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging in Chronic Inflammatory Demyelinating Polyneuropathy

Abstract: Diffusion tensor imaging yields valid quantitative biomarkers in CIDP and might aid in diagnosis with high diagnostic accuracy. Fractional anisotropy and RD may serve as parameters of myelin sheath integrity, but AD is unable to reflect axonal damage in CIDP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
85
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 41 publications
12
85
0
2
Order By: Relevance
“…Inflammation and edema can lead to an increased ADC value. As expected, the TN and CPN of GBS patients showed a significant decrease in FA and an increase in ADC values, which were consistent with the results of Breckwoldt et al, Wu et al, and Kronlage et al The AD value provides information about the integrity of axons. Haakma et al concluded that the decreases in AD values were associated with axonal degeneration.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Inflammation and edema can lead to an increased ADC value. As expected, the TN and CPN of GBS patients showed a significant decrease in FA and an increase in ADC values, which were consistent with the results of Breckwoldt et al, Wu et al, and Kronlage et al The AD value provides information about the integrity of axons. Haakma et al concluded that the decreases in AD values were associated with axonal degeneration.…”
Section: Discussionsupporting
confidence: 91%
“…The axial diffusion coefficient (AD) and radial diffusion coefficient (RD) values mean the eigenvalues when water diffuses along and perpendicular to the long axis of the fiber bundle, respectively. These two parameters were also used in recent studies to detect the functional changes in peripheral nerves …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Still, electrophysiological data are a prerequisite to diagnose CIDP and diagnosis cannot be based on HRUS data. However, different opinions about the suitability of NCS for patient follow‐up were described previously . Progression of disease can be approached by NCS by showing deterioration of myelination or secondary axonal loss.…”
Section: Discussionmentioning
confidence: 99%
“…However, different opinions about the suitability of NCS for patient follow-up were described previously. [27][28][29] Progression of disease can be approached by NCS by showing deterioration of myelination or secondary axonal loss. In our study, we found significant changes of NCS parameters in progressive CIDP only for a decrease of the CMAP amplitudes of the tibial and median nerve at a few time points.…”
Section: Discussionmentioning
confidence: 99%